ONLINE BANKING SERVICES OF PUBLIC SECTOR BANKS AT KOVILPATTI TOWN (International Journal of Food and Nutritional Sciences, 2023)
The emergence of new banking technology creates highly competitive market conditions, which have a critical impact upon customer behaviour. Hence, it is the need of the hour for the banking sector, to better understand their customers and their attitudes toward technology in general, to enhance increased satisfaction of their customers using online banking. If they succeed, banks will be able to influence and even determine customer behaviour, which will become a major issue in creating competitive advantage in the future. The tools used for this study is chi-square test. The study focused on the online banking services of public sector banks operating in kovilpatti town with an objective of getting valuable suggestions to take strategic decisions and its implementation.